IN VITRO PROTEIN DIGESTIBILITY OF MILLET BASED SOUTH INDIAN BREAKFAST PREPARATIONS - V. DURGA RANI, JANE BRIDGET KANDEH, UMA DEVI K K. UMA MAHESWARI, T. SARAH KAMALA and (The Journal of Research, PJTSAU, 2019)
Millet grains are now receiving specific attention from the point of nutrition security and the importance of utilization millets as food is increasing in the 21st Century. Six varieties of millets have been developed and standardized to serve as most common breakfast dishes namely idly, dosa and upma using traditional recipe. The overall mean IVPD of idlys from 6 millets was 78.67Â±4.36% and IVPD of millet idly was significantly high (P